Bio-Analytical Method Development for Estimation of Levofloxacin: Application in Estimation of Drug in Nano-formulations and Pharmacokinetic Studies - Maurya, Priyanka; Kumar, Abhiram; Singh, Samipta; Nisha, Raquibun; Pal, Ravi Raj; Chourasia, Manish Kumar; Saraf, Shubhini Awasthi (Indian Journal of Pharmaceutical Education and Research, 2021)
Aim/Background: Levofloxacin is a safe antibiotic for various inflammatory disorders and a rapid analytical method for various samples reduces the estimation time as well as injects efficiency in the system. The developed method uses minimal solvents with least preparation time also helps in reducing the errors generated by the analyst during processing. Materials and methods: RP-HPLC method was developed for estimation of levofloxacin using Box Behnken Design. The PDA detector was set at 295nm with a run time of 6 mins. The samples were run at binary gradient mode with 35% phase B. The mobile phase consisted of acetate buffer, acetonitrile and methanol. Linearity was established for pure drug as well as spiked plasma samples. Drug extraction from plasma samples was done by liquid-liquid extraction using acetonitrile and methanol. Results: The developed method has a retention time of 3.1± 0.41 mins and is validated as per ICHQ2R1 guidelines. The standard curve indicates high correlation with a R2 value of 0.9999. The robustness (RSD<2) and system suitability studies indicate that it is a stable method with high specificity as determined with different samples. The LOD and LOQ were found to be 0.08ppm and 0.25ppm respectively indicating estimations of samples with a low drug content. Conclusion: A rapid, robust, selective, simple and sensitive method was developed and validated for quick estimation of levofloxacin in different sample. The significant reduction in retention time obtained by the developed method proves its efficiency in tapping the mobile phase costs as well as expediting the analytical process. The DOE optimised method is suitable for rapid estimation of levofloxacin in plasma as well as nanoformulations.
Keywords: Bioanalytical method; Robustness; Specificity; Stability; ICHQ2R1